IPTEKS INFORMASI BIAYA DALAM PENGGUNAAN PRODUK E-CHANNEL PADA BANK RAKYAT INDONESIA (PERSERO) TBK - Tumbel, Jinnyfer J.F; Pondaag, Naomi G.H; Karamoy, Herman (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
In this modern era, technological developments are experiencing very rapid development. Likewise in financial institutions, namely banks, technology is now a determinant of bank progress and provides benefits in transactions and in carrying out the operations of other banks. And if the bank does not prioritize technology in its operations, banks will find it difficult to move forward and develop to find good profits or profits for the development of the bank. For this reason, banks issue e-channel products that are very useful, and make it easier for people not only to help the community but also to be profitable and bring good profits to the bank, and in the use of e-channel products, of course there are costs truncated which may not be recognized by the general public, but in it is also very beneficial to both parties. Keywords: cost information, e-channel products